Trouble finding the optimal AdS/QCD - Veschgini, Kambis; Megías Fernández, Eugenio; Pirner, Hans J. (Physics letters, 2011)
In the bottom-up approach to AdS/QCD based on a five-dimensional gravity dilaton action the exponential of the dilaton field is usually identified as the strong or 't Hooft coupling. There is currently no model known which fits the measurements of the running coupling and lattice results for pressure at the same time. With a one parametric toy model we demonstrate the effect of fitting the pressure on the coupling and vice versa.